Cerium and erbium effects on Daphnia magna generations: A multiple endpoints approach. (November 2019) - Galdiero, E.; Carotenuto, R.; Siciliano, A.; Libralato, G.; Race, M.; Lofrano, G.; Fabbricino, M.; Guida, M.
Abstract: Cerium (Ce, CeCl3 ) and Erbium (Er, ErCl3 ) are increasingly used in many electronic devices facilitating the alteration of their biogeochemical cycles (e.g. e-waste). Previous surveys stated that their environmental concentrations due to natural or anthropogenic events can reach up to 161 μg/L in ore mine effluent for Ce with a mean water concentration of 0.79 μg/L, and 11.9 μg/L for Er in ore mine effluents with a mean water concentration of 0.004 μg/L. Their potential effects onto aquatic organisms are still relatively unexplored. In this study, long-term multigenerational effects on Daphnia magna were assessed using various exposure times (3, 7, 14, and 21 days) in three generations (F0, F1 and F2). Each generation was exposed to environmental concentrations of Ce and Er (0.54 and 0.43 μg/L, respectively – mean values) and effects included organisms' size, parental reproduction, and survival, determination of reactive oxygen species (ROS), enzymatic activity (superoxide dismutase (SOD), catalase (CAT), and glutathione S-transferase (GST)), gene expression of ATP-binding cassette (ABC) transporter, and uptake. Results evidenced that chronic multi-generational exposure of daphnids to Ce and Er reduced survival, growth and reproduction, decreasing ROS, SOD and CAT from F0 to F2. Ce reduced the number of generated offsprings after each generation, while Er delayed the time of offsprings emergence, but not their number. ROS, SOD, CAT and GST evidenced that Er is slightly more toxic than Ce. Up- and downregulation of genes was limited, but Ce and Er activated the ABC transporters. Uptake of Ce and Er decreased through exposure time and generations. Graphical abstract: Image 1 Highlights: Toxicity of Ce and Er to D. magna chronic multigenerational test was evaluated. Long-term generational exposure evidenced toxic effects with uptake events. Ce reduced generated offsprings in F0-2, while Er delayed offsprings emergence. Ce and Er rendered organisms more susceptible to oxidative stress. ATP binding cassette showed an uptake-ejection equilibrium for Ce and Er in F0-2.